2023
DOI: 10.3892/ijmm.2023.5313
|View full text |Cite
|
Sign up to set email alerts
|

Flavin containing monooxygenase 2 regulates renal tubular cell fibrosis and paracrine secretion via SMURF2 in AKI‑CKD transformation

Longfei Wang,
Hongchu Zha,
Jing Huang
et al.

Abstract: In the follow-up of hospitalized patients with acute kidney injury (AKI), it has been observed that 15-30% of these patients progress to develop chronic kidney disease (CKD). Impaired adaptive repair of the kidneys following AKI is a fundamental pathophysiological mechanism underlying renal fibrosis and the progression to CKD. Deficient repair of proximal tubular epithelial cells is a key factor in the progression from AKI to CKD. However, the molecular mechanisms involved in the regulation of fibrotic factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This is evidenced by the fact that the overexpression of Smurf2 has been shown to encourage the activation of the TGF-β-responsive promoter and induce EMT within human kidney cortical epithelial cells ( 107 ). Recent research has demonstrated that flavin-containing monooxygenase 2 can enhance the expression of Smurf2 and facilitate its nuclear translocation, resulting in tubular cell fibrogenesis and paracrine secretion ( 110 ). In addition, the E3 ligase, Arkadia/RNF111, regulates TGF-β signaling by degrading Smad7 ( 111 , 112 ).…”
Section: Ptms Of Tgf-β1 Signalingmentioning
confidence: 99%
“…This is evidenced by the fact that the overexpression of Smurf2 has been shown to encourage the activation of the TGF-β-responsive promoter and induce EMT within human kidney cortical epithelial cells ( 107 ). Recent research has demonstrated that flavin-containing monooxygenase 2 can enhance the expression of Smurf2 and facilitate its nuclear translocation, resulting in tubular cell fibrogenesis and paracrine secretion ( 110 ). In addition, the E3 ligase, Arkadia/RNF111, regulates TGF-β signaling by degrading Smad7 ( 111 , 112 ).…”
Section: Ptms Of Tgf-β1 Signalingmentioning
confidence: 99%